HUBUNGAN GANGGUAN FUNGSI PENGHIDU DAN STATUS GIZI PADA LANSIA DI PUSAT SANTUNAN KELUARGA DI JAKARTA BARAT - Beatus Bibang; Jimmy Fransisko Abadinta Barus; Yuda Turana (Bahasa Indonesia, 2020)
Introduction: The prevalence of individuals who experience an impaired olfactory function increases with age. Impaired olfactory function is considered as one of the risk factors for malnutrition in the elderly. The purpose of this study was to examine whether there was a relationship between impaired olfactory function and nutritional status in the elderly. Methods: Comparatives analytical study with a cross-sectional approach to the elderly group. Subjects were recruited from Pusat Santunan Keluarga/PUSAKA (in the period May-June 2016) at Jakarta Barat. Subjects were chosen by random sampling. The nutritional status, cognitive, and olfactory function were assessed with MNA assessment, MMSE instrument, and olfactory assessment. Result: 207 people participated in this study; 67.1% were women. Impaired olfactory function and malnourished were found in 46.5% and 42.5%, respectively. The bivariate analysis found that there was a relationship between olfactory function and nutritional status (p=0,006), olfactory function and MMSE score (p=0,001). Logistic regression analysis demonstrated that there were no significant associations between olfactory function and nutritional status with the variables examined in this study. Conclusion: Olfactory function is not directly associated with nutritional status in the elderly.